The mediating role of employee engagement in the influence of career path development and talent management practices on employee intention to stay among generation Z employees - Dewi, Ni Putu Ariska; Rahyuda, Agoes Ganesha (International research journal of management, IT and social sciences, 2025)
This study aims to examine the role of employee engagement mediation in the influence of career path development and talent management practices on employee intention to stay in Generation Z employees at PT BSH. The main theoretical foundation used is Social Exchange Theory (SET), which emphasizes the importance of the mutual relationship between the organization and employees. This study uses a quantitative approach. The population in this study is all generation Z employees who work at PT BSH, with a total sample of 195 respondents selected through purposive sampling techniques. Data collection was carried out using a structured questionnaire distributed online. The data analysis tool used is Partial Least Squares Structural Equation Modeling (PLS-SEM) which is processed with the help of SmartPLS 4.0 software. The results of the analysis show that career path development and talent management practices have a positive and significant effect on employee intention to stay, both directly and through employee engagement mediation. Employee engagement has been proven to have a significant role as a complementary partial mediation variable in this model.